Diversity of Herbaceous Plant in The Utilization Block of Sumber Agung Tahura Wan Abdul Rachman Bandar Lampung - Widia Paramita; Yulianty Yulianty; Bambang Irawan; Suratman Suratman (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2019)
Diversity is a variety of species that are similarly formed and the abundance of a species. The purpose of this study is to determine the diversity and characteristics of herbaceous plants in Sumber Agung Resort Bandar Lampung Wan Abdul Rachman (WAR) forest park. The method used is a purposive sampling method at several points, done by direct observation using the Belt Transect method with plot size 1x1 m² with a distance between plot 100 m² then the picture of herbaceous plants taken as documentation material. The species is then taken for identification regarding some literature. Data analysis by measuring the parameters of vegetation using the analysis of density and frequency variables which then determine the Importance Value Index (INP). Observation of herbaceous plants was done by identifying and making herbarium. The results of the study are, there are 45 species of herbaceous plants that have been identified, consisting of 22 families. The highest density of herbaceous species that are found belongs to Asteraceae, Solanaceae, Araceae, Poaceae, Zingiberaceae, and Euphorbiaceae. Characteristics of herbaceous growth are influenced by air temperature, soil moisture, and soil pH. The highest Important Value Index (INP) in herbaceous plants belongs to Family Poaceae; Lophatherium gracile with an important value index (INP) 31.43%.